Application of a portable primary standard level graphite calorimeter for absolute dosimetry in a clinical low-energy passively scattered proton beam. (21st November 2022) - Lourenço, A; Lee, N; Shipley, D; Romano, F; Kacperek, A; Duane, S; Cashmore, M; Bass, G; Palmans, H; Thomas, R
Abstract: Objective . A calibration service based on a primary standard calorimeter for the direct determination of absorbed dose for proton beams does not exist. A new Code of Practice (CoP) for reference dosimetry of proton beams is being developed by a working party of the UK Institute of Physics and Engineering in Medicine (IPEM), which will recommend that ionisation chambers are calibrated directly in their clinical beams against the proposed Primary Standard Proton Calorimeter (PSPC) developed at the National Physical Laboratory (NPL). The aim of this work is to report on the use of the NPL PSPC to directly calibrate ionisation chambers in a low-energy passively scattered proton beam following recommendations of the upcoming IPEM CoP. Approach . A comparison between the dose derived using the proposed IPEM CoP and the IAEA TRS-398 protocol was performed, and k Q values were determined experimentally for three types of chambers. In total, 9 plane-parallel and 3 cylindrical chambers were calibrated using the two protocols for two separate visits. Main results . The ratio of absorbed dose to water obtained with the PSPC and with ionisation chambers applying TRS-398 varied between 0.98 and 1.00, depending on the chamber type. The new procedure based on the PSPC provides a significant improvement in uncertainty where absorbed dose to water measured with a user chamber is reported with an uncertainty of 0.9% (1 σ ), whereas the TRS-398 protocol reports an uncertainty of 2.0% and 2.3% (1 σ ) for cylindrical and plane-parallel chambers, respectively. The k Q values found agree within uncertainties with those from TRS-398 and Monte Carlo calculations. Significance . The establishment of a primary standard calorimeter for the determination of absorbed dose in proton beams combined with the introduction of the associated calibration service following the IPEM recommendations will reduce the uncertainty and improve consistency in the dose delivered to patients.